The possibility of application of salam in Malaysian Islamic banking system - Muneeza, Aishath; Nik Yusuf, Nik Nurul Atiqah; Hassan, Rusni (Emerald Group Publishing Limited, 2011)
Purpose – This research aims to explore the theoretical nature of salam contract in depth, the extent of its use in the banking arena of Malaysia and to test the theoretical feasibility of its future application by the Islamic banks in Malaysia by suggesting an Islamic banking product structure based on salam contract.